Meningkatkan Durasi Perilaku On-Task Terhadap Tugas Akademik Menggunakan Teknik Shaping - Maria Weni Gowasa; Rani Rafika Duri; Nurhasni Nurhasni; Tiara Tri Ariani; Yuli Rahmadini; Muhammad Iqbal Firmansyah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
On-task behavior problems are a common obstacle in the academic activities of school-aged children. Children often experience difficulty maintaining attention, are easily distracted, and exhibit frequent shifts of attention during learning. This has the potential to lead to decreased academic achievement and increased impulsive behavior. This study aims to determine the effectiveness of the shaping behavior modification technique in increasing the duration of on-task behavior. The subject of the study was a 4-year-old boy who exhibited attention problems while working on academic tasks. The research design used a one-group pretest-posttest design with a single-subject approach using an A-B-A data collection model. Data collection was carried out using a duration data sheet to measure the duration of on-task behavior through direct observation. Data analysis was conducted by comparing the average duration of on-task behavior before and after the intervention. The results showed that the shaping technique did not provide a significant increase in the duration of on-task behavior. Although there were fluctuations in the duration of increases and decreases during the intervention phase, these results were not sufficient to prove the effectiveness of shaping in this context. These findings indicate that the shaping approach is less than optimal when applied alone, and that additional intervention methods or other alternatives are needed that are more appropriate to the characteristics and needs of the child. This research provides implications for the importance of selecting appropriate and adaptive behavioral intervention techniques to help children improve focus and engagement in academic activities.